Commercial Bank Liability Management and Monetary Control - Theilman, Ward (Journal of Financial and Quantitative Analysis, 1970)
In recent years, large commercial banks in the United States have turned to so-called “liability management” as a way to acquire additional funds. The use of Certificates of Deposit (CD's), Eurodollar balances, debentures, and recently the issuing of commercial paper through their holding companies represent an extension of the more traditional secondary reserve asset management approach to bank liquidity and reserve adjustment.